Low-cost facility for assessing impact of carbon dioxide on crops - Chakrabarti, B.; Singh, S.D.; Naresh Kumar, Soora; Aggarwal, Pramod K.; Pathak, Himanshu; Nagarajan S (2012)
A low-cost free-air carbon dioxide enrichment (FACE) system has been developed at the Indian Agricultural Research Institute, for assessing the climate change impacts on crops. In the FACE system, the supply and monitoring of CO2 is regulated by the computer-based SCADA system. Carbon dioxide concentration recorded at 5 min intervals varied from 507 to 559 ppm in an hourly period. Monthly mean values of CO2 concentration inside the ring ranged from 525 to 553 ppm from July to April. Crops grown inside the FACE ring showed increased yield over ambient CO2 condition. The operating cost of the system is US$ 100 m–2 yr–1, which is much less compared to similar setups in other countries.